Penentuan retensi nitrogen dan energi metabolis kulit pisang raja (Musa paradisiaca) fermentasi dengan Rhizopus oligosporus pada ransum broiler - Kalalo, M.N; Wolayan, F.R.; Imbar, M.R.; Liwe, H. (Universitas Sam Ratulangi, 2021)
DETERMINATION OF NITROGEN RETENTION AND METABOLIC ENERGY OF BANANA PEELS (Musa paradisiaca) FERMENTATION WITH Rhizopus oligosporus ON BROILER RANSOM. Banana peel is a waste that has the potential to be used as feed because it is abundant and has the nutrients needed by livestock. This study aims to determine protein consumption, nitrogen retention value (RN) and nitrogen-corrected metabolic energy (AMEn) value of broiler rations containing unfermented plantain peel flour and fermented broiler rations with Rhizopus oligosporus mold. This research was conducted using 20 broilers of strain Arbor Acres CP 707 aged 5 weeks. The design used was Student's t-test which consisted of 2 treatments, each treatment consisting of 10 broilers as replications. The rations used in this study were rations containing plantain peel flour without fermentation and rations containing fermented plantain peel flour with Rhizopus oligosporus mold. The results of the analysis of diversity showed that the treatment between no fermentation and fermentation was significantly different for protein consumption (P <0.05), nitrogen retention was significantly different (P <0.05) and the value of metabolic energy was significantly different (P <0.05). The T-Student test results for the protein consumption value of nitrogen retention values showed that the treatment without fermentation was 63.59% and 71.87% fermented products with Rhizopus oligosporus mold. The metabolic energy values in the treatment without fermentation were 2336.6 Kcal / kg and 2732.4 Kcal / kg in fermentation products with Rhizopus oligosporus mold. Based on the results of this study it can be concluded that the use of fermented plantain peel products with Rhizopus oligosporus in broiler rations can increase protein consumption, nitrogen retention, and metabolic energy of broiler chickens.Key words: plantain peel, fermentation, Rhizopus oligosporus, broiler chicken.